The Hidden Self Behind the Screen: The Role of Social Support in Self-Discrepancy? - Desmiranahari, Alya; Wina Lova Riza; Dinda Aisha (Psikoislamedia: Jurnal Psikologi, 2025)
Users of roleplay accounts on social media exhibit interaction patterns that encourage the construction of ideal identities alongside the free expression of alternative identities. This study aims to investigate the influence of social support on self-discrepancy. Employing a quantitative approach with a causal associative design, the research involved 339 roleplay account users. Instruments utilized included the Multidimensional Scale of Perceived Social Support (Zimet et al., 1988) and a Self-Discrepancy scale based on Higgins’ (1987) theory, adapted by the researcher. Results indicate a significant positive effect of social support on self-discrepancy, accounting for 21.3% of the variance. Higher perceived social support correlates with greater self-discrepancy. These findings suggest that social support does not uniformly yield positive outcomes, particularly when individuals experience pressure to conform to expectations within virtual identities. This study contributes significantly to advancing theoretical understanding of social support mechanisms in digital environments and provides an empirical basis for developing adaptive mental health interventions tailored to the complexities of social media interactions.  Keywords: Social Support, Virtual Identity, Social Media, Roleplay, Self-Discrepancy